2018
DOI: 10.1093/ejo/cjy048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic medication on root resorption associated with orthodontic tooth movement: a systematic review of animal studies

Abstract: PROSPERO (CRD42017078208).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 79 publications
0
22
0
1
Order By: Relevance
“…Regarding the latter, root resorption was shown to decrease after administering ibuprofen and meloxicam in low doses. However, no difference was noted in the cases of paracetamol and aspirin . The other review presented information on the administration of analgesics for a duration of more than 2 weeks, which is not consistent with the usual clinical practice in case of pain experienced due to orthodontic procedures.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the latter, root resorption was shown to decrease after administering ibuprofen and meloxicam in low doses. However, no difference was noted in the cases of paracetamol and aspirin . The other review presented information on the administration of analgesics for a duration of more than 2 weeks, which is not consistent with the usual clinical practice in case of pain experienced due to orthodontic procedures.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, systematic reviews have elaborated on the potential effects of medication used for the relief of pain on orthodontic tooth movement and associated root resorption in experimental animals . Regarding the latter, root resorption was shown to decrease after administering ibuprofen and meloxicam in low doses.…”
Section: Introductionmentioning
confidence: 99%
“…Unselektive NSAID sollten daher während einer kieferorthopädischen Therapie nach Möglichkeit nicht eingesetzt werden. In Studien zeigte sich jedoch als interessanter Nebeneffekt eine signifikante Reduktion therapieassoziierter Zahnwurzelresorptionen unter Einfluss von NSAID, welcher in Zukunft einen Ansatz für eine gezielte pharmakologische Prävention von Zahnwurzelresorptionen in speziellen Fällen darstellen könnte [5,6]. Können Antibiotika unerwünschte Nebenwirkungen im Rahmen einer kieferorthopädischen Therapie entfalten?…”
Section: Antwortunclassified
“…According to clinical trials observation, SMV intake was beneficial for chronic periodontitis control for its function in inflammation limitation and periodontal tissues repair 9‐11 . Animal studies have shown that SMV when administered systemically resulted in increased tooth anchorage and reduced root resorption 3,12 . To be mentioned, the pocket injection of 1.2% SMV gel decreased space re‐opening after orthodontic space closure in human anterior teeth 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Animal studies have shown that SMV when administered systemically resulted in increased tooth anchorage and reduced root resorption. 3,12 To be mentioned, the pocket injection of 1.2% SMV gel decreased space re-opening after orthodontic space closure in human anterior teeth. 13 We thus assume a bone anabolic property of SMV on periodontal tissue under a biomechanically induced inflammatory condition.…”
mentioning
confidence: 99%